Psychometric properties of clock and pelvic drawings in Parkinson's disease: A validity and cross‐sectional study. (14th May 2019) - Abraham, Amit; Wright, Gene N.; Morrison, Margaret W.; Hart, Ariel; Dickstein, Ruth; Hackney, Madeleine E.
Abstract: Objectives: Parkinson's disease (PD) is characterized by visuospatial and body schema deficits. People with PD often exhibit hypometric movements and graphic hypometria (i.e., small drawing dimensions). The goal of the current study was to explore graphic‐metric representation in people with PD by assessing pelvic and clock drawing dimensions (i.e., height and width) and by investigating associations between pelvic drawing dimensions and participant characteristics. Methods: Twenty people (16 males, 4 females; M age: 65.75 ± 10.13 years) with idiopathic PD (Hoehn &Yahr Stages I–III) volunteered to participate in this study. Draw Your Pelvis and Clock Drawing tests were used for assessing drawing dimensions, which were then correlated with PD severity, stage and duration, cognitive level, side of symptoms onset, and pelvic schema score. Bivariate and multiple linear regression analyses were also used. Results: Excellent (.844–.999) interrater reliability was shown for measuring pelvic and clock drawing dimensions. Pelvic drawing dimensions did not significantly ( P  > .05) differ in magnitude, whereas clock drawing height was significantly ( p  < .01) greater than width, both suggesting graphic dysmetria (i.e., distorted graphic dimensions). Pelvic drawing width was negatively associated with PD severity and stage, was positively associated with pelvic schema score, and predicted all three parameters. Conclusion: Measuring pelvic drawing dimensions, and specifically pelvic drawing width, holds potential as an adjunct diagnostic measure in PD assessments and for detecting pelvic schema deficits or misperceptions. This test can be used by physical therapists in the clinic for assessing disease severity, stage, and pelvic schema in people with PD. The knowledge gained from this study contributes to a greater understanding of graphic‐metric representation and associated deficits in people with PD. Future studies should explore the relationship between pelvic drawing dimensions and pelvic mentally imaged estimates, and their role in motor planning, control, and execution in people with PD.